Increasing concentration of major crops in China from 1980 to 2011 - Fang Yin; Zhanli Sun; Liangzhi You; Daniel Müller (Journal of Land Use Science [ISSN:] 1747-4248, 2018)
The concentration of crop cultivation can be measured in terms of spatial clustering and of inequality in the distribution of the cropland area. We used official agricultural statistics at the county level (N~=~2,354) for each year from 1980 to 2011 for all of China to analyse the changes in spatial clustering and inequality of overall cropland and of the harvested areas of the five major crops (rice, maize, wheat, soybean, and potato). We quantified the spatial clustering with global and local Moran's I and assessed the inequality in the distribution of crop cultivation with the generalized entropy index. The results showed that the cropland area and harvested areas of the major crops indeed became more homogeneous over time, and the major crops concentrated in fewer areas and in the major historic breadbaskets. Increasing concentration may offer opportunities in specialization and positive agglomeration effects but can reduce the resilience of food systems and agricultural sustainability.
Keywords: 330; land use; spatial clustering; spatial heterogeneity; crop production; Moran's I; Generalized Entropy Index (GEI); inequality